Functional and structural assessment of lamellar macular holes. Issue 3 (19th December 2012) - Parravano, Mariacristina; Oddone, Francesco; Boccassini, Barbara; Chiaravalloti, Adele; Scarinci, Fabio; Sciamanna, Marta; Boninfante, Antonluca; Tedeschi, Massimiliano; Varano, Monica
Abstract : Aim: The purpose of the present work was to evaluate the macular sensitivity of patients with lamellar macular hole (LMH) by means of microperimetry, and to explore the relationships between macular function, LMH anatomical characteristics and vitreous status. Methods: A total of 39 eyes from 37 patients with a diagnosis of LMH and 20 age-matched control subjects were enrolled. All patients underwent a complete ophthalmological examination including visual acuity testing (logMAR) and MP1 microperimetry. LMHs were quantitatively and qualitative characterised by spectral domain optical coherence tomography (OCT) in terms of base and apex diameter, depth, central foveal and perifoveal thickness, splitting location and integrity of outer retina layers. B scan ultrasonography was performed in order to characterise the vitreoretinal relationships. Results: Mean total (17.2±2.2 vs 19.6±0.5 dB, respectively, p<0.0001) and mean central (16.1±3.2 vs 19.2±0.7 dB, p<0.0001) retinal sensitivity were significantly reduced in LMH eyes in comparison with controls. Best corrected visual acuity (BCVA) (0.15±0.15 vs 0.03±0.06 logMar, p=0.001) and central retinal thickness (329.05±59.3 vs 265±28.5 μm, p<0.0001) were significantly worse in LMH eyes in comparison with controls. In our population, mean total and central retinal sensitivity showed a moderately significant relationship with LMH depth (R 2 0.18, p=0.006, R 2 0.14, p=0.02, respectively). In all, 38% of LMH eyes (15/39) showed focal interruptions of the inner–outer segment junction with lower values of BCVA and macular sensitivity. An incomplete posterior vitreous detachment with vitreopapillary adhesion was found in 48.7% (19/39) of patients with LMH. Conclusions: Eyes with LMH show an impaired macular function, which is partially related to LMH depth and is more pronounced in eyes with outer retinal layers abnormalities.